Safety and effects of a home-based Tai Chi exercise rehabilitation program in patients with chronic heart failure: study protocol for a randomized controlled trial - Jiao, Qian; Meng, Chao; He, Haoqiang; Li, Shanshan; Xu, Fan; Cui, Weilu; Lou, Yuqing; Li, Zining; Ma, Jing; Sun, Di; Wu, Huidong; Li, Haixia (Frontiers in Cardiovascular Medicine, 2023)
Introduction Chronic heart failure (CHF), as the final stage of the progression of many cardiovascular disorders, is one of the main causes of hospitalization and death in the elderly and has a substantial impact on patients' quality of life (QOL). Exercise-based cardiac rehabilitation (CR) has been shown to considerably enhance QOL and prognosis. Given the barriers to center-based CR faced by most developing countries in the form of expensive instruments, the development of home-based CR is necessary. Tai Chi, as an instrument-free exercise, has been shown to be successful in treating elderly CHF individuals. Fu Yang, as one of the academic concept of Traditional Chinese Medicine (TCM), believes that the fundamental pathogenesis of CHF is the gradual decline of Yang, and emphasizes the restoration of Yang physiological function in the treatment process. Therefore, we develope a home-based Tai Chi exercise rehabilitation program called Fu Yang Tai Chi (FYTC) for elderly CHF patients by combining the Fu Yang Theory of TCM with the CR theory. The objective of this study is to evaluate the effectiveness, acceptability, and safety of the program. Methods and analysis We suggest conducting a parallel randomized controlled clinical trial with open label. Eighty CHF elderly participants will be randomly assigned in a 1:1 ratio to the FYTC rehabilitation program group or the moderate-intensity aerobic walking control group. Eligible participants will engage in either three sessions weekly of FYTC or walking exercise for 12 weeks. The primary outcome is the relative change in 6 min walk distance (6MWD). The secondary outcomes are the plasma levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP), QOL, left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDd), self-rating anxiety scale (SAS) and depression scale (SDS), exercise skills, and noninvasive hemodynamic monitoring. Throughout the trial, adverse events will be recorded for safety evaluation. Researchers who are blinded to the treatment allocation will analyze the data. Ethics and dissemination This research was authorized by the Guang'anmen Hospital Ethics Committee of the Chinese Academy of Medical Sciences (2022-141-KY). Our findings will be shared online and in academic conferences as well as in peer-reviewed journals. Trial registration number ChiCTR2200063511.